Telework, the Timing of Work, and Instantaneous Well-Being: Evidence from Time Use Data - J. Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2018)
In this paper, we analyze the time allocation decisions of teleworkers, and compare them with their commuter counterparts. Using data from the American Time Use Survey for the years 2003 to 2015, we analyze the time spent working, the timing of work, and the instant enjoyment experienced while working, of teleworkers and commuters. Results show that teleworkers devote 40% less time to market work activities than do commuters, and less than 60% of both male and female teleworkers work at 'regular hours', vs around 80% of similar commuters. A higher percentage of teleworkers than commuters are engaged in leisure and non-market work at the central hours of the day. Using additional information from the Well-being Module for the years 2012 and 2013, we find that male teleworkers experience higher levels of satisfaction while working than do commuters, net of differences in socio-demographic and job characteristics. Our results point towards male telecommuters being happier in their job tasks than commuters, which may lead to a higher productivity of the former, and explains why teleworkers are able to work fewer hours per day.
Keywords: D13; J22; 330; telework; market work time; instantaneous well-being; American Time Use Survey